Impact investment fund aimed at restoring and improving biodiversity and ecosystems in Brazil initialized by CIAT and CCAFS - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
CCAFS and CIAT, with support from USAID and together with Mirova NaturalCapital, successfully co-designed, developed and participated as a cornerstone investor for the Amazon Biodiversity Fund for Brazil. This fund is an impact investment fund targetting USD 100 million of investment which is focused on reducing deforestation, reducing emissions, building resilient livelihoods and protecting critical biodiversity.